Study on Relationship between Contact Stress Distribution Characteristic and Fatigue Spalling of Angular Contact Ball Bearing at High Speed - Chao Wan; Kang Zhang; Zeyu Tian; Xiangmin Chen; Luping Li (Jixie chuandong)
Fatigue spalling is one of the main failure forms of bearing， and the change of contact stress between rolling body and raceway is an important factor causing fatigue spalling of bearing. Taking the angular contact ball bearing as study object， based on the classical pseudo-statics model， considering the effect of inertia force on the rolling body under the condition of high rotation speed， the internal geometry relationship and force balance relationship expression of angular contact ball bearings are built， the characteristic parameters of the bearing at high speed are obtained through solving the model by numerical method. The accuracy of the model is verified by comparing the characteristic parameters to the literature. On this basis， the axial force， the radial force and the speed of rotation are respectively controlled， and the distribution characteristics and changes of the contact stress of the bearing under special working conditions are studied， and the relationship between the variation of the external load and the speed of rotation and the fatigue spalling of the bearing is obtained， which provides certain technical guidance for reducing fatigue spalling of bearing.